Witchtown - Oakes, Cory Putman (Boston ; Houghton Mifflin Harcourt, 2017)
When they arrive in Witchtown, everything changes for a teenager and her mother, who travel to witch-only communities, lying, cheating, and stealing everything they can--leaving behind only a powerful spell that erases them from the memories of everyone they have ever met.